Public pensions and immigration policy when voters are differently skilled - Tim Krieger (Nordakademie - Hochschule der Wirtschaft, 2004)
Although immigration of workers generates a positive externality on members of domestic pension systems, many countries are very reluctant to allow foreigners into their labor markets. In a political economic framework, we explain this voting outcome by considering a young unskilled median voter who faces - in addition to a reduction of contribution rates - negative effects from immigration as well.
Keywords: J61; H55; 330; pensions; immigration; median voter; skill differences; Gesetzliche Rentenversicherung; Rentenfinanzierung; Einwanderung; Median Voter; Unterschicht; Theorie